Intravenous lidocaine for postmastectomy pain treatment: randomized, blind, placebo controlled clinical trial - Couceiro,Tania Cursino de Menezes (2015)
BACKGROUND AND OBJECTIVE: Postoperative pain treatment in mastectomy remains a major challenge despite the multimodal approach. The aim of this study was to investigate the analgesic effect of intravenous lidocaine in patients undergoing mastectomy, as well as the postoperative consumption of opioids. METHODS: After approval by the Human Research Ethics Committee of the Instituto de Medicina Integral Prof. Fernando Figueira in Recife, Pernambuco, a randomized, blind, controlled trial was conducted with intravenous lidocaine at a dose of 3 mg/kg infused over 1 h in 45 women undergoing mastectomy under general anesthesia. One patient from placebo group was. RESULTS: Groups were similar in age, body mass index, type of surgery, and postoperative need for opioids. Two of 22 patients in lidocaine group and three of 22 patients in placebo group requested opioid (p = 0.50). Pain on awakening was identified in 4/22 of lidocaine group and 5/22 of placebo group (p = 0.50); in the post-anesthetic recovery room in 14/22 and 12/22 (p = 0.37) of lidocaine and placebo groups, respectively. Pain evaluation 24 h after surgery showed that 2/22 and 3/22 patients (p = 0.50) of lidocaine and placebo groups, respectively, complained of pain. CONCLUSION: Intravenous lidocaine at a dose of 3 mg/kg administered over a period of an hour during mastectomy did not promote additional analgesia compared to placebo in the first 24 h, and has not decreased opioid consumption. However, a beneficial effect of intravenous lidocaine in selected and/or other therapeutic regimens patients cannot be ruled out.